Ozone control as a novel method to improve health-promoting bioactive compounds in red leaf lettuce (Lactuca sativa L.) - Lee, Jin-Hui; Goto, Eiji (Frontiers in Plant Science, 2022)
In this study, we determined the short-term effects of ozone exposure on the growth and accumulation of bioactive compounds in red lettuce leaves grown in a controlled environment plant factory with artificial light, also known as a vertical farm. During cultication, twenty-day-old lettuce (Lactuca sativa L. var. Redfire) seedlings were exposed to 100 and 200 ppb of ozone concentrations for 72 h. To find out how plants react to ozone and light, complex treatments were done with light and ozone concentrations (100 ppb; 16 h and 200 ppb; 24 h). Ozone treatment with 100 ppb did not show any significant difference in shoot fresh weight compared to that of the control, but the plants exposed to the 200 ppb treatment showed a significant reduction in fresh weight by 1.3 fold compared to the control. The expression of most genes in lettuce plants exposed to 100 and 200 ppb of ozone increased rapidly after 0.5 h and showed a decreasing trend after reaching a peak. Even when exposed to a uniform ozone concentration, the pattern of accumulating bioactive compounds such as total phenolics, antioxidant capacity and total flavonoids varied based on leaf age. At a concentration of 200 ppb, a greater accumulation was found in the third (older) leaf than in the fourth leaf (younger). The anthocyanin of lettuce plants subjected to 100 and 200 ppb concentrations increased continuously for 48 h. Our results suggest that ozone control is a novel method that can effectively increase the accumulation of bioactive compounds in lettuce in a plant factory.